Acute Myocardial Infarction (AMI) as the Effect Modifiers to Modify the Association Between Red Blood Cell Distribution Width (RDW) and Mortality in Critically Ill Patients With Stroke - Guo, Tongli; Qin, Zuoan; He, Dian (Frontiers in Medicine, 2022)
Abstract Background and Objectives: Few studies have evaluated the impact of red blood cell distribution width (RDW) on prognosis for critically ill patients with acute stroke according to recent studies. The aim of this study was to investigate the association between RDW and mortality in these patients. Methods:Clinical data were extracted from the eICU Collaborative Research database(eICU-CRD) and analyzed. The exposure of interest was RDW measured at admission. The primary outcome was in-hospital mortality. Binary logistic regression models and interaction testing were performed to examine the RDW-mortality relationship and effect modification by acute myocardial infarction and hypertension(HP) . Results: Data from 10022 patients were analyzed.In binary logistic regression analysis,after adjusting for potential confounders, RDW was found to be independently associated with in-hospital mortality[odds ratio (OR) 1.07, (95% confidence interval (CI) 1.03 to 1.11); p = 0.001].Higher RDW linked to an increase in mortality (OR, 1.07; 95% CI, 1.03 to 1.11; P for trend <0.0001) . Subgroup analysis showed that in patients combined with AMI and without HP (both P-interaction＜0.05), the correlation between RDW and in-hospital mortality is stronger (AMI group: OR, 1.30;95% CI,1.07 to 1.58, not AMI group: OR,1.06; 95% CI, 1.02, 1.10; HP group: OR, 0.98; 95%CI,0.91 to 1.07, not HP group: OR,1.09; 95%CI, 1.05 to 1.14). Conclusions: A higher baseline RDW is independently correlated with prognosis in critically ill patients with acute stroke, and the correlation can be modified by AMI and HP duration.